Altered intestinal barrier contributes to cognitive impairment in old mice with constipation after sevoflurane anesthesia - Tianyun Zhao; Tianyun Zhao; Junming Lu; Jingwen Qin; Yanxin Chen; Ziwen Shi; Wei Wei; Peng Xiong; Daqing Ma; Daqing Ma; Xingrong Song; Xingrong Song; et al. (Frontiers in Nutrition, 2023)
BackgroundElderly patients have a high risk of developing postoperative cognitive dysfunction (POCD). Gastrointestinal disorders, such as constipation, in the elderly population may be involved in the pathogenesis of neurological disorders by promoting inflammatory responses due to a ‘leaky gut’. General anesthetic sevoflurane may impair gastrointestinal function in elderly patients to trigger neurological complications following surgery. Therefore, we hypothesized that elderly individuals with gastrointestinal dysfunction may be more vulnerable to sevoflurane and consequently develop POCD.MethodsAged mice were randomly divided into four groups: control (CTRL), CTRL+sevoflurane (Sev), slow transit constipation (STC), and STC + Sev. Mice in the STC and STC + Sev groups were intra-gastrically administrated loperamide (3 mg/kg, twice a day for 7 days) to induce a slow transit constipation (STC) model determined with fecal water content and the time of first white fecal pellet, whereas mice in the other groups received the similar volume of saline. One week later, mice in the CTRL+Sev group and STC + Sev group received 2% sevoflurane for 2 h. The gut permeability evaluated with 4-kDa fluorescein isothiocyanate (FITC)-dextran, serum cytokines, microglia density, TLR4/NF-κB signaling expression, and POCD-like behavioral changes were determined accordingly.ResultsThe loperamide-induced STC mice had decreased fecal water content and prolonged time of first white fecal pellet. Sevoflurane exposure caused significantly increased gut permeability and serum cytokines, as well as the activation of microglia and the TLR4/NF-κB signaling pathway in the prefrontal cortex of the aged STC mice. Sevoflurane also caused cognitive impairment and emotional phenotype abnormality in aged STC mice.ConclusionAged STC mice were more vulnerable to sevoflurane anesthesia and consequently developed POCD-like behavioral changes. Our data suggest that gastrointestinal disorders including constipation may contribute to the development of POCD.